Use of lexical chunk approach in teaching writing - Ismail, Razalina (2015)
The objectives of this study were to investigate how the lexical chunk approach can be used in teaching writing to KPTM students, improve their performance in writing skill and determine students’ perception of the lexical chunk approach in writing. This is a descriptive study that combined both qualitative and quantitative designs. A total of 48 students taking diploma courses at Kolej Poly-Tech Mara, Bangi were selected as sample using purposive sampling method. The field work carried out for twelve weeks. The instruments used in this study include written test taken from question bank, interview and demographic questionnaire which had been validated by two experienced lecturers. Prior to the actual research work, a pilot study was carried out using 15 KPTM students. In answering the first research question, thorough explanation on how the lexical chunk approach was taught in writing class was given, including the teaching materials used in accomplishing the mission. For the second research question, it was clear that the students managed to write good and comprehensible sentences using lexical chunks, apart from being exposed to new chunks of words and other useful words and phrase for their essay. The ferment treatment using the lexical chunk approach taught to the students was found to have successfully helped them give good input in their essays. To answer the last research question on the students’ perception in the use of the lexical chunk approach in writing, two students were randomly selected from each group (low, average and high scores). All the interviewees gave good and positive feedback on the lexical chunk approach introduced to them although some of them claimed that they had difficulties in learning to use this approach at the beginning. The thesis is concluded by giving implications and suggestions for future study.